Use of defatted chia seeds to enhance the nutritional quality of wheat pasta - Aranibar, Carolina (2016)
Fil: Aranibar, Carolina. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Ciencia y Tecnología de los Alimentos Córdoba; Argentina.